The influence of weather conditions on German armour during Operation “Barbarossa” in the Soviet Union from June to December 1941 - Michalski, Hubert (Armia kontra natura, 2020)
German tanks were not prepared for the weather conditions that prevailed in the autumn and winter of 1941 in the Soviet Union. Frequent engine failures caused by dust required a long repairs. During the winter, the vehicles got stuck in the snow, making it impossible to continue the attack. The Germans took steps to modernize the construction of their tanks so that they could cope better in heavy terrain, mud and deep snow.